Work-life conflict experienced by Turkish women managers during the Covid-19 pandemic: A qualitative research - Erdirençelebi, Meral; Çini, Mehmet Akif; Ertürk, Ebru; Baykal, Elif (Ege University, Faculty of Economics and Administrative Sciences (FEAS), 2022)
The changes in business life during the Covid 19 Pandemic had a significant effect on work-life balance of individuals, especially women as their roles at home and work have increased and the conflict between these roles has become more pronounced. Considering this fact, this research aimed to determine the conflicts and changes on the work-life balance of female managers during the Covid-19 pandemic. In this context, the research was carried out within the framework of workplace responsibilities, private life responsibilities, work-private life conflict, and the effects of the Covid-19 pandemic. This research was carried out in educational institutions of Turkey, through interviews with 16 married women employees who have children. The obtained data were classified following the main purpose of the research and content analysis, then coded and analyzed using the MAXQDA.The findings showed that the dominant factor in the pandemic period was Work-Life conflict and job responsibilities restricted private life responsibilities more. The fact that working at home decreases productivity, low productivity extends working hours, and the negative effects of technology increasing the workload have caused female managers, who are aware of their job responsibilities, to work more.
Keywords: Covid-19 Pandemic; Women Managers; Work-Life Conflict; Social Roles; Family Responsibilities; Work Responsibilities